Isolation and structure elucidation of two antiprotozoal bisbenzylisoquinoline alkaloids from Triclisia gilletii stem bark. (December 2018) - Cimanga Kanyanga, R.; Kikweta Munduku, C.; Nsaka Lumpu, S.; Tshodi Ehata, M.; Makila Bool-Miting, F.; Kambu Kabangu, O.; Mbamu Maya, B.; Cos, P.; Maes, L.; Vlietinck, A.J.; Tuenter, E.; Foubert, K.; et al.
Graphical abstract: Highlights: In vitro and in vivo antiplasmodial activity of Triclisia gilletii extracts. Isolation and structure elucidation of (−)-phaeanthine and (−)-pycmanilline. In vitro antiplasmodial activity of (−)-phaeanthine and (−)-pycmanilline. Abstract: An aqueous decoction of stem bark of Triclisia gilletii (De Wild.) Staner (Menispermaceae) is used in several African countries to treat various diseases including malaria. The aqueous extract and the total alkaloid extract were evaluated in vitro for their antiplasmodial activity against the chloroquine-resistant Plasmodium falciparum strain K-1, the chloroquine-sensitive strain NF54 A19A, and in vivo in mice infected with P. berghei berghei and P. yoelii N67. Both extracts were active in vitro with IC50 values of 0.75 and 0.25 μg/ml against P. falciparum K1, respectively; and 1.15 and <0.02 μg/ml against P. falciparum NF54 A19A, respectively. With regard to the in vivo activity, at the highest oral dose of 400 mg/kg body weight, the aqueous and the total alkaloid extracts produced 73.0% and 80.7% chemosuppression against P. berghei berghei, respectively, while against P. yoelii N67, a chemosuppression of 70.1%, and 78.4%, respectively, was observed. Two bisbenzylisoquinoline alkaloids were isolated from the total alkaloid extract, i.e. (–)-pycmanilline and (–)-phaeanthine in a yield of 0.20% and 0.40%, respectively. They were active in vitro against P. falciparum K-1 (IC50 1.6 ± 0.3 and 0.8 ± 0.3 μM, respectively), and P. falciparum NF54 A19 A (IC50 0.07 ± 0.01 and 0.03 ± 0.01 μM, respectively). Also against other protozoa IC50 values in the micromolar range were observed. (–)-Pycmanilline is reported for the first time.